(untitled) (CIPEEX, 2025)
This study aimed to associate the regular consumption of ultra-processed foods (UPF) with the sleep quality of civil servants of the Federal Network for Professional, Scientific and Technological Education (FNPSTE). This is a cross-sectional epidemiological study with a quantitative approach, carried out in November 2022. There were 1,563 participants in the sample, including teachers and administrative technicians in education from all regions of Brazil. A questionnaire designed by the authors was used to collect data, covering sociodemographic issues and lifestyle habits. The data was analyzed using descriptive statistics and Poisson regression, with the prevalence ratio as the measure of effect, with 95% confidence intervals (CI) and α = 0.05. Regular Consumption (RC) is defined as consumption ≥ 5 days a week. RC of UPF was observed in 15.4% of men and 13.9% of women. A significant association was found in individuals aged ≤ 35 years (p = 0.043) who reported sleeping less than 6 hours per night (p = 0.037), who reported being dissatisfied with the quality of their sleep (p < 0.001), and who did not regularly practice physical activity (p < 0.001). These findings encourage the use of policies and programs to reduce UPF consumption and the practice of regular physical activity to improve sleep quality.